Characterization and Antitumor Activity Study for a Therapeutically Important L-glutaminase Purified from Staphylococcus Aureus - Gh. AL-Juhaishy. Asmaa A. Hussein, Mustafa (International Journal of Psychosocial Rehabilitation, 2020)
The L-glutaminase enzyme produced under optimum conditions in a previous study was purified using precipitation with 80% saturation of ammonium sulfate, ion exchange chromatography on a DEAE-cellulose column, and filtration gel chromatography during the Sephadex G-200 column. The specific activity of the purified enzyme after the last step was raised to 1000 U/mg for 38.4-fold purification and 69% enzyme recovery. The MWut. of purified l-glutaminase was estimated through S.D.S.-P.A.G.E. to be 35 kDa. It gave the highest activity at pH 8.0 and stability at pH 7.5. The enzyme was active at 37°C and stable at a range of temperatures from 20°C to 37°C. Also, L-glutaminase activity was inhibited to 62% in the presence of CaCl₂.. L-glutaminase was tested for in-vitro cytotoxic activity using the MTT assay against the colorectal adenocarcinoma (LS 174T) cell line, which was inhibited with an IC50 of 37.19 IU/ml; however, it didn’t show an important effect on normal cells.